EXPERIMENTAL INVESTIGATION OF THE INFLUENCE OF AQUEOUS SOLUTION COMPOSITION ON THE ELASTIC PROPERTIES OF SANDSTONE AT HIGH PRESSURE AND TEMPERATURE AND COMPUTER MODELING OF WATER-ROCK INTERACTION - Lebedev E.B.; Ryzhenko B.N.; Dorfman A.M.; Zebrin S.R.; Zharikov A.V.; Sokolova N.T.; Burkhardt H. (My University, 1999)
Recent geophysical studies demonstrated the occurrence of zones with unusually low seismic velocities and high electric conductivity in the middle part of the Earth's crust. The nature of such zones is not fully understood. Some researchers speculated on their possible link to changes in the porosity and permeability of rocks and to the presence of fluids. To test this hypothesis, an experimental investigation was carried out to assess the influence of fluid on the elastic properties of sandstone under temperature and pressure characteristic of the middle levels of the continental crust. The experiments were performed at a pressure of 300 MPa and temperatures up to 850°C. The results revealed that solution composition has a substantial effect on the elastic properties of sandstone. The reactions of solutions (neutral, acidic, and alkalic) with rock resulted in changes in the microscopic texture of the rock and, consequently, changes in its elastic properties. Computer modeling was also undertaken in order to estimate changes in the composition of the fluid phase and mineral proportions of the rock. Together with studies of the role of volatile components in geochemical processes, these results provide a basis for comprehensive petrophysical and geochemical interpretations of geophysical data related to the middle continental crust.